SOCIAL REHABILITATION THROUGH STREET ENTREPRENEURSHIP: AN INTEGRATED MODEL AND RESEARCH AGENDA - Suresh, Reshmi V; Kumar, S. Rajitha (International Journal of Psychosocial Rehabilitation, 2020)
Purpose –Entrepreneurship plays a vital role in generating employment opportunities and poverty eradication in developing countries across the globe. But the interaction of the entrepreneurship domain and sociology domain is limited. The purpose of this paper is to develop an integrated model of entrepreneurial intention and social rehabilitation and to propose the theoretical base for such interactions. Design/methodology/approach – The study explores various manifestations of informal(street) entrepreneurship by incorporating differentclassical andemerging theories. The economic well-being and psychological well-being dimensions of social rehabilitation are considered for conceptualisation. The data has been collected through field visits and face to face interviews from 68 street vendors in southern India. Findings – The present study opens a vast arena for future researchers to empirically test the proposed research model within the informal entrepreneurial contexts.The study clearly states the significance of developmental policies towards subsistent entrepreneurs who belong to the lower sections of the society. Research limitations/implications – This paper shows the need to move beyond considering entrepreneurship as an endeavour at the corporate level. Practical implications – By unraveling the interaction of informal entrepreneurship with social rehabilitation, the present study aims at employment generation and poverty eradication. Also, the study gives foundations for the government’s policy-level interventions in enhancing the skills of street vendors for attaining social rehabilitation. Originality/value – The present research paper is a pioneer attempt to study the interactions of street entrepreneurship and social rehabilitation.